2020
DOI: 10.48550/arxiv.2006.01078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deflection Angle and Shadow Behaviors of Quintessential Black Holes in arbitrary Dimensions

A. Belhaj,
M. Benali,
A. El Balali
et al.

Abstract: Motivated by M-theory/superstring inspired models, we investigate certain behaviors of the deflection angle and shadow geometrical shapes of higher dimensional quintessential black holes associated with two values of the dark energy (DE) state parameter, being ω = − 1 3 and ω = − 2 3 . Concretely, we derive the geodesic equation of photons on such backgrounds. Thanks to the Gauss-Bonnet theorem associated with the optical metric, we compute the leading terms of the deflection angle in the so-called weak-limit … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…More recently, these thermodynamical properties have been combined with optical ones in order to unveil such phase transitions [42]. These optical aspects, concerning the shadow and the deflection angle, have been discussed using different approaches [10,11]. In particular, it has been revealed that the shadows of non-rotating black holes involve a circular geometry [43].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, these thermodynamical properties have been combined with optical ones in order to unveil such phase transitions [42]. These optical aspects, concerning the shadow and the deflection angle, have been discussed using different approaches [10,11]. In particular, it has been revealed that the shadows of non-rotating black holes involve a circular geometry [43].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing where one has used λ = √ 65536M 2 4 − 6π 2 6 + 256M 2 . It has been observed that this behavior changing of the deflection angle, in terms of the charge, appears in the case of the quintessential RN black hole [27]. However, this is removed in the case of RN ordinary black holes.…”
Section: Deflection Angle Behaviors By Reissner-nordström Ads Black H...mentioning
confidence: 96%
“…This optical quantity could unveil certain data which may impose particle physics constraints associated with black hole detections. In particular, many works on such optical aspects have been conducted [24][25][26][27][28]. An inspection shows that this optical quantity has been approached using different methods.…”
Section: Introductionmentioning
confidence: 99%
“…In this subsection, we study the effect of the parameters of the theory on the emission of particles around the black hole given by solution (8). It was shown that the black hole shadow corresponds to its high energy absorption cross section for the observer located at infinity [77][78][79]. In fact, at very high energies, the absorption cross-section oscillates around a limiting constant value σ lim which is approximately equal to the area of the photon sphere (σ lim ≈ πr 2 s ).…”
Section: B Energy Emission Ratementioning
confidence: 99%